Founder management, government ownership and firm performance : Evidence from malaysia - Irene, Wei Kiong Ting; Kweh, Qian Long; Hooi, Hooi Lean; Sui, Hai Juan (University of Malaya, 2018)
This paper examines first, how founder CEOs affect firm performance and second, whether government ownership moderates the relationship between founder CEOs and firm performance of companies listed in Malaysia between 2002 and 2011. Firms led by founder CEOs perform better than those led by non-founder CEOs. Although a direct-effect test indicates that government ownership may be detrimental to firm performance, there exists a positive relationship between founder CEOs and firm performance in the presence of government ownership from the perspective of growth opportunities. In terms of profitability, however, government ownership may not increase return on assets. These findings suggest that the government may play a crucial role to protect investor’s wealth, especially with respect to long-term survival of a company.